BUSINESS INCUBATION THROUGH THE EYES OF SMES: PERCEIVED VALUE, SUPPORT MECHANISMS, AND ENTREPRENEURIAL MEANING-MAKING - Dwi Erlin Effendi (Resilience of Small Medium Business, 2025)
Objective: This study aims to explore the perceptions of MSME actors regarding the value of business incubation, the forms of support they receive during the incubation process, and how these experiences shape their understanding of entrepreneurship. This study stems from the need to understand business incubation not only from an institutional perspective, but also from the perspective of business actors as beneficiaries. Research Design & Methods: This study uses an exploratory qualitative approach with in-depth interviews with 30 SME actors from various sectors who have participated in business incubation programs. The data is analyzed using a phenomenological approach to reveal the dimensions of value perception, the most influential forms of support, and the process of meaning construction experienced during incubation. Findings: The results of the study indicate that SME entrepreneurs view business incubation as a process that provides value in the form of improved managerial capacity, market access, networking, and business legitimacy. The most meaningful support includes intensive mentoring, practical training, and access to strategic stakeholders. Furthermore, incubation facilitates the formation of new meaning in the role of entrepreneurship, namely the transition from conventional business actors to strategic and visionary entrepreneurs. Implications & Recommendations: These findings suggest that incubator institutions should design approaches that are more adaptive and based on the specific needs of SMEs. Integration between technical guidance and psychosocial reinforcement is needed in incubation programs to encourage a comprehensive transformation of the role of entrepreneurs. Public policy should also support the sustainability of community-based incubation programs and cross-sector partnerships. Contribution & Value Added: This study contributes to the entrepreneurship literature by emphasizing the importance of subjective dimensions in evaluating the effectiveness of business incubation, as well as introducing a meaning-making perspective in the context of SME development. The study also provides practical insights for policymakers and incubator managers to design more impactful interventions oriented toward long-term transformation.